2018
DOI: 10.3136/fstr.24.223
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Chemoenzymatic Removal of Heavy Metals in Sea Cucumber <i>Acaudina leucoprocta</i>

Abstract: Sea cucumbers are traditional marine food in Asian countries. In this work, the chemical elements accumulated in sea cucumber Acaudina leucoprocta from the East China Sea were measured and analyzed. The contents of Zn, Mn, Cu, As, Pb, Cd and Cr increased with the increase of weight of A. leucoprocta. The levels of Pb and As in all the examined individuals were higher than the maximum residue limits (MRLs) permitted in foodstuffs. The metals were found to be selectively distributed in the body compartments of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Fretes et al (2020) showed that the accumulation of heavy metals in the intestine of Stichopus herrmanni caused damage to villi in the form of necrosis. The body wall of Acaudina leucoproctais apt to absorption and accumulation of heavy metals, which may be considered as a precious bioindicator for assessing and monitoring metals contamination in surrounding seawater (Lin et al, 2018). The amount of Hg in the muscles of Holothuria leucospilota from Karachi coasts in Pakistan was found to be less than its skin (Ahmed and Bat, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fretes et al (2020) showed that the accumulation of heavy metals in the intestine of Stichopus herrmanni caused damage to villi in the form of necrosis. The body wall of Acaudina leucoproctais apt to absorption and accumulation of heavy metals, which may be considered as a precious bioindicator for assessing and monitoring metals contamination in surrounding seawater (Lin et al, 2018). The amount of Hg in the muscles of Holothuria leucospilota from Karachi coasts in Pakistan was found to be less than its skin (Ahmed and Bat, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Mohammadizadeh et al (2016) found that Cu and Zn amounts in Holothuria leucospilota and Holothuria scabra from the northern part of Qeshm Island, Persian Gulf were below permissible limits, but Cd and Pb amounts were much higher than the permissible limits for human consumption. Similarly, Pb and As amounts in Acaudina leucoprocta from the East China Sea were above the maximum residue limits permitted in foodstuffs (Lin et al, 2018). Hashmi et al (2014) determined Pb, Cd, Zn, Cu, Cr and Mn levels in eight sea cucumber species from the market in Kota Kinabalu, Sabah.…”
Section: Co In Sea Cucumbersmentioning
confidence: 97%
See 1 more Smart Citation
“…However, As (>0.5 mg/kg) (Mohammadizadeh et al, 2016). This is due to both of these compartments direct contacted with the sediments that presence of heavy metals by feeding or buried themselves in the sediments and their body wall is vulnerable to accumulate and absorption metal ions (Lin et al, 2018). This information proven that benthos has the potential as bioindicator in reducing the amount of heavy metals in water column and within the sediments (Ahmed, Mohammad Ali and Bat, 2017).…”
Section: Bioaccumulation Of Metal Ionsmentioning
confidence: 99%
“…However, due to long living in the submarine silt, its body wall is covered by dense and stiff dirt, in which seabed silt and mucus secreted from the surface of A. leucoprocta were strongly linked, influencing the food value of A. leucoprocta (Shan et al, 2013). Additionally, rapid developments of industrialization and urbanization have generated severe marine pollution, causing increased contents of toxic heavy metals (As, Hg, Pb, and Cd) in the surface of A. leucoprocta (Lin et al, 2018). The consumption of A. leucoprocta has been drastically hampered (Huang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%